Free Radical Scavenging Capacities and Alleviating Actions of Polysaccharides Extract of Termitomyces le-testui on Methylprednisolone-Induced Immunodepression in Rats - Foncham Evans Ngwenah; Kada Sanda Antoine; Salah Martin; Tume Christopher; Oumar Mahamat (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Natural products have been said to show immunomodulatory and antioxidant activities. The research study was aimed to assess the immunomodulatory and free radical scavenging activities of crude polysaccharide from dry mushroom fruiting bodies of Termitomyces le-testui. Materials and Methods. Hot water extract of polysaccharide extract of T. le-testui was prepared and tested in white albino Wister rats for its immunomodulatory activities effect on methylprednisolone-immunosuppressed animals. In addition, the radical scavenging activity of the polysaccharide was evaluated using nitrite and hydrogen peroxide. Results. The result of the study showed that the polysaccharide T. le-testui increases the phagocytic index, energy metabolism of macrophages, spleen index, and nitric oxide in a concentration-dependent manner in immunosuppressed animals. Also, it was observed that the extract increased dose-dependent total oxidative stress and thymus index. Finally, the crude polysaccharide-rich extract showed nitrite and hydrogen peroxide scavenging activity in a concentration-dependent manner. Conclusion. Polysaccharide-rich extract possesses immunomodulatory and antioxidant properties.